Exploring the contemplative : A meditative self-inquiry of Individual Consultations practice - Bak, Tao (Journal of Academic Language and Learning, 2025)
Reflective practice is routinely used to enhance the development of skills and understandings in professional settings. The contemplative-spiritual perspective is a recent addition to more traditional forms of reflection. This approach views education as encounter, learning as a journey, and sees value in placing emphasis on embodied experience of learning and knowing. A Meditative Inquiry frame is adopted in this paper to combine autoethnography and journaling to present a contemplative reflective self-study of the author’s academic language and learning (ALL) practice. The author’s background as a member of a contemplative practice community, in this case a Steiner or Waldorf School community, is examined, in addition to thematic analysis of journal entries collected over 18 months. Themes identified include working with a wider sense of the person, bringing heart, being present, the notion of living thinking and language and the indirect ‘imparting’ that occurs within Individual consultations practice. A braided narrative allows switching between memories, journal entries and point of writing reflections. The contribution lies in the innovative approach to reflection modelled and the bringing of contemplative studies perspectives to bear on ALL practice. Themes presented are offered as potential departure points for ways of thinking through ALL practice, rather than definitive insights or conclusions.